Young workers and the job-swapping phenomenon - Cregan, Christina [Verfasser] (My University, 1991)
"This paper suggests that the job-swapping phenomenon associated with new entrants to the workforce marks part of a social adjustment process in the transition to adult working life in which young people, by virtue of their age and inexperience and the jobs in which they work, embark on a series of separations. The data-set under investigation consists of a survey of a single cohort of 1922 early school-leavers from manual backgrounds in London, 1979-1981. Job-swapping as an adjustment process was identified for a minority; non-whites were more separation-prone than whites, but there were no gender differences. The effect of the process on change in income over the period of the survey was evident for males but not for females; this seemed to be the result of the different characteristics of gender-based markets." (author's abstract) ((en)) Der Beitrag untersucht die Bedeutung des Arbeitsplatzwechsels bei der Berufseinmündung von Jugendlichen. Dazu wurden im Rahmen von Wiederholungsbefragungen 1922 Jugendliche interviewt, welche vorzeitig die Schule abgebrochen hatten. Die Untersuchungsergebnisse zeigen, dass der Arbeitsplatzwechsel nur für eine Minderheit der Jugendlichen eine Rolle bei der Berufseinmündung spielt. (IAB)
Jugendliche und Arbeitsplatzwechsel
Keywords: P 2.1.1 Ohne Schulabschluss; P 2.1 Schulabgänger; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; Schulabbrecher; Arbeitsplatzwechsel; Arbeiter; Jugendlicher; Schulabgänger; Berufseinmündung; Auswirkung; Einkommen; Quantitative Angaben